-.166(x-18)+0.5(x+2)=x+12

Simple and best practice solution for -.166(x-18)+0.5(x+2)=x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.166(x-18)+0.5(x+2)=x+12 equation:


Simplifying
-0.166(x + -18) + 0.5(x + 2) = x + 12

Reorder the terms:
-0.166(-18 + x) + 0.5(x + 2) = x + 12
(-18 * -0.166 + x * -0.166) + 0.5(x + 2) = x + 12
(2.988 + -0.166x) + 0.5(x + 2) = x + 12

Reorder the terms:
2.988 + -0.166x + 0.5(2 + x) = x + 12
2.988 + -0.166x + (2 * 0.5 + x * 0.5) = x + 12
2.988 + -0.166x + (1 + 0.5x) = x + 12

Reorder the terms:
2.988 + 1 + -0.166x + 0.5x = x + 12

Combine like terms: 2.988 + 1 = 3.988
3.988 + -0.166x + 0.5x = x + 12

Combine like terms: -0.166x + 0.5x = 0.334x
3.988 + 0.334x = x + 12

Reorder the terms:
3.988 + 0.334x = 12 + x

Solving
3.988 + 0.334x = 12 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3.988 + 0.334x + -1x = 12 + x + -1x

Combine like terms: 0.334x + -1x = -0.666x
3.988 + -0.666x = 12 + x + -1x

Combine like terms: x + -1x = 0
3.988 + -0.666x = 12 + 0
3.988 + -0.666x = 12

Add '-3.988' to each side of the equation.
3.988 + -3.988 + -0.666x = 12 + -3.988

Combine like terms: 3.988 + -3.988 = 0.000
0.000 + -0.666x = 12 + -3.988
-0.666x = 12 + -3.988

Combine like terms: 12 + -3.988 = 8.012
-0.666x = 8.012

Divide each side by '-0.666'.
x = -12.03003003

Simplifying
x = -12.03003003

See similar equations:

| y=x^2+18+95 | | 8x=4x+4 | | 3x+48=6x+6 | | x^2-9x+16=8 | | .01x-7=13 | | 3.56+458+49.6= | | 16(2x-5)=4(8x+1) | | 4+13p-1=8p+53-5p | | 400-6.59= | | 4x^2+13+9=0 | | x^2+5x-27=9 | | 5s+12s=85 | | -9.8x=68.6 | | y=-x^2+3x+10 | | n*n-1=15 | | 20t=-56 | | 8n=-40 | | -6(2b+3)+(13b-4)=0 | | 4x^2-5x+4=8x+1 | | x*x+6x-16=0 | | 5.9q-2.3-5.8q=-0.9-5.3 | | 6x^2-25x-9=0 | | -5y+6=-6y+1 | | 6(x-4)+80=-2x | | z-45=-35 | | 2(4)5y=23 | | 3f+2=17 | | 3f+2= 17 | | 14-10x=-26 | | 8=4+2q | | 8 = 4 + 2 q | | y-5(3)=9 |

Equations solver categories